2014
DOI: 10.1111/bph.12744
|View full text |Cite
|
Sign up to set email alerts
|

Functional plasticity of the N/OFQ‐NOP receptor system determines analgesic properties of NOP receptor agonists

Abstract: Despite high sequence similarity between NOP (nociceptin/orphanin FQ opioid peptide) and opioid receptors, marked differences in endogenous ligand selectivity, signal transduction, phosphorylation, desensitization, internalization and trafficking have been identified; underscoring the evolutionary difference between NOP and opioid receptors. Activation of NOP receptors affects nociceptive transmission in a site-specific manner, with antinociceptive effects prevailing after peripheral and spinal activation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
185
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(191 citation statements)
references
References 258 publications
(422 reference statements)
6
185
0
Order By: Relevance
“…Spinal morphine produced a dose dependent and robust antinociceptive effect in line with previous findings (Kosson et al, 2008). A similar antinociceptive action has been promoted by the spinal injection of N/OFQ accordingly to (Schroder et al, 2014;Zeilhofer and Calò, 2003;). Compared to morphine, N/OFQ displayed similar potency but reduced maximal effects.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Spinal morphine produced a dose dependent and robust antinociceptive effect in line with previous findings (Kosson et al, 2008). A similar antinociceptive action has been promoted by the spinal injection of N/OFQ accordingly to (Schroder et al, 2014;Zeilhofer and Calò, 2003;). Compared to morphine, N/OFQ displayed similar potency but reduced maximal effects.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover the action of N/OFQ was behaviorally selective; in fact the administration of analgesic doses of morphine promoted scratching responses in monkeys while N/OFQ did not. This evidence suggests the existence of relevant species differences regarding the therapeutic potential of NOP agonists as spinal analgesics (Schroder et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…Given that capsaicin-sensitive nerve fibers are involved in a variety of pain conditions, the full effectiveness of BU08028 in inhibiting capsaicin-induced allodynia may indicate its clinically relevant analgesic efficacy. In addition, rodent studies have demonstrated the analgesic efficacy of NOP-related agonists across diverse pain modalities, including inflammatory pain, neuropathic pain, and sickle cell pain (18,20,22,29). Cumulative evidence supports a broad application of NOP-related agonists as analgesics.…”
Section: Discussionmentioning
confidence: 99%
“…(17)(18)(19)(20). Following spinal and systemic administration, NOP receptor agonists produce antinociception and antihypersensitivity comparable to those of MOP receptor agonists, but without reinforcing effects in nonhuman primates (21)(22)(23)(24).…”
mentioning
confidence: 99%
“…across a variety of pain assays. Systemic or supraspinal administration in rodents does not produce antinociception against an acute thermal stimulus (tail flick, hot plate), but may have positive effects in inflammatory, neuropathic, and chronic pain states (for reviews, see Mogil and Pasternak, 2001;Lambert, 2008;Schröder et al, 2014).…”
Section: Introductionmentioning
confidence: 99%